2010
DOI: 10.4103/0253-7613.71926
|View full text |Cite
|
Sign up to set email alerts
|

Effect of l-ornithine l-aspartate against thioacetamide-induced hepatic damage in rats

Abstract: Objective:To investigate the hepatoprotective activity of L-ornithine-L-aspartate against thioacetamide (TAA)-induced hepataopathy in rats.Materials and Methods:The hepatoprotective activity of L-ornithine-L-aspartate (OA) at a dose of 2 g/kg, p.o. for 10 days was evaluated against TAA (250 mg/kg, i.p. for 2 days) induced hepatopathy in rats. Biochemical parameters such as serum aspartate transaminase, alanine transaminase, alkaline phosphatase, bilirubin and glutathione, thiobarbituric acid reactive substance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
20
1
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 20 publications
7
20
1
4
Order By: Relevance
“…Our results appear to confirm the hepato‐protective activity of LOLA in human with hepatic impairment caused by the decrease in hepatic perfusion after TIPSS . One explanation of this result was that LOLA most likely had effects against loss of functional integrity of the cell membranes of hepatocytes caused by hepatotoxins such as hypoperfusion …”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Our results appear to confirm the hepato‐protective activity of LOLA in human with hepatic impairment caused by the decrease in hepatic perfusion after TIPSS . One explanation of this result was that LOLA most likely had effects against loss of functional integrity of the cell membranes of hepatocytes caused by hepatotoxins such as hypoperfusion …”
Section: Discussionsupporting
confidence: 79%
“…Hence, further confirmations in studies with large sample size are needed. One previous experiment study showed that LOLA had hepato‐protective activity against thioacetamide‐induced hepatic damage in rats . And, Grungreiff et al .…”
Section: Discussionmentioning
confidence: 97%
“…The nervous system also has low level of defense repair mechanisms and very high oxygen consumption against oxidative injurynisms and very high oxygen consumption against oxidative injury (Halliwell et al, 1985). Our study in agreement, with different studies showed that the administration of PLF extract decrease the severity of hepatic encephalopathy owing to TAA intoxication, indicating that free radicals and reactive oxygen species have an important role in the pathogenesis of hepatic encephalopathy (Velvizhi et al, 2002) Najmi et al, (2010, SomayaZakaria et al, (2009). In the present study, malonaldehyde (MAD) contents of hepatic and brain tissues and nitric oxide (NO) of brain tissue were significantly increased in rats adminstrated with TAA as compared to the control rats.…”
Section: Discussionsupporting
confidence: 89%
“…Discussing the possible mechanism associated with this improvement is beyond the scope of this study. Nevertheless, LOLA administration was shown before to improve liver function in rats by strengthening the endogenous antioxidant defense and reducing thiobarbituric acid‐reactive species, as well as maintaining liver cell membrane integrity . Also, though not tested in this trial, a 30‐day LOLA course was shown to be able to modulate neural activation in patients with MHE, improving central nervous system oxygenation and cognitive function .…”
Section: Discussionmentioning
confidence: 81%